Kinerja Sistem Agroforestri pada Areal Ijin Perhutanan Sosial: Studi Kasus Kelompok Tani Hutan Argo Makmur Lestari, Tulungagung - Utomo, Singgih; Purwanto, Agus Budi; Prasetyo, Eko; Maulana, Ahdiar Fikri; Arifriana, Ridla; Lestari, Puji; Ngadianto, Agus (Universitas Pattimura, 2025)
The objective of this study is to provide a comprehensive description of the performance of agroforestry systems in the Community Forest (HKm) scheme, as implemented by the Argo Makmur Lestari Forest Farmers Group in Tulungagung, East Java. A qualitative descriptive approach was utilised to facilitate the collection of data through field observations and in-depth interviews with farmers and group administrators. The results indicate that the agroforestry system in KTH AML has been adopted by some farmers, with motivations including income diversification, labor efficiency, strengthening social relations, and increasing soil fertility. The present study has demonstrated that the implementation of agroforestry systems has a beneficial effect on the environment, as evidenced by the increase in plant biodiversity (12 species) in comparison to monoculture systems (1 species). Additionally, the pH level of soil in agroforestry systems (5.5–6.5) exceeds that of soils cultivated under monoculture systems (4.5–5.5). This finding suggests that the agroforestry system has the potential to enhance soil fertility. Nevertheless, the advancement of agroforestry adoption remains encumbered by challenges, namely the reliance on established corn commodity infrastructure and the inadequate access to agroforestry commodity markets. It is imperative that the internal strength of the KTH AML institution is reinforced, in conjunction with the external assistance programs, in order to expedite the transition from monoculture systems to agroforestry systems. These findings carry significant implications for the development of contextual and responsive agroforestry models.